The Anecdotal Archive: Building Design, Oral History, and the Notion of an Alevi Place of Worship. (1st January 2022) - Andersen, Angela
Scholarly investigation of communities with oral teaching traditions and vernacular building designs must step beyond established research frameworks for Islamic religious architecture to challenge typological and document-based categorizations of monumental buildings. Alevism's student-teacher based socio-religious structure and service-oriented approaches to community life and religious expression, both in Turkey and in other parts of the world, shape interpretations of ceremonial cemevis, the houses of the cem ceremony. Alevi discussions of this architecture must play a significant role in the scholarly analysis of these sites. In this article, I emphasize the role of oral history in architectural studies by conducting interviews with architects who have participated in design competitions and contributed to a dialogue on a nascent contemporary Alevi monumental idiom. The article also highlights the considerations that arise in the course of examining both traditional and modern Alevi spaces, and reflects on the role of engagement with Alevis when researching cemevis and ceremonial settings.